2020
DOI: 10.1002/hec.4141
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sugar‐sweetened beverage taxes on purchases: Evidence from four city‐level taxes in the United States

Abstract: Since 2017, many US cities have implemented taxes on sugar‐sweetened beverages to decrease consumption of sugary beverages and raise revenue. We analyze household receipt data to examine the impact of taxes on households' beverage purchases in the four largest US cities with such taxes: Philadelphia, PA; San Francisco, CA; Seattle, WA; and Oakland, CA. We compare changes in monthly household purchases in the treatment cities with changes in two comparison groups: (1) areas adjacent to the treatment cities or (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 24 publications
4
38
1
Order By: Relevance
“…This is one of the first studies to combine information about SSB and other beverage purchasing, with and without SSB taxation, across multiple cities using a single household-level data source. It is consistent with one other multi-city analysis, which used a different data source and analytic method, and also found that SSB purchasing reduction was concentrated in Philadelphia [ 33 ]. It is the first such study to investigate differential effects by household income and differences in switching behavior that might occur due to different taxation details (i.e., the size and applicability of the tax).…”
Section: Discussionsupporting
confidence: 87%
“…This is one of the first studies to combine information about SSB and other beverage purchasing, with and without SSB taxation, across multiple cities using a single household-level data source. It is consistent with one other multi-city analysis, which used a different data source and analytic method, and also found that SSB purchasing reduction was concentrated in Philadelphia [ 33 ]. It is the first such study to investigate differential effects by household income and differences in switching behavior that might occur due to different taxation details (i.e., the size and applicability of the tax).…”
Section: Discussionsupporting
confidence: 87%
“…Association of a Sweetened Beverage Tax With Purchases of Beverages and High-Sugar Foods calories purchased per person. Although a number of prior studies in Philadelphia have shown increased prices and purchase declines, 11,14,15,20,21 this is the first study, to our knowledge, in a US taxed jurisdiction to show sustained, 2-year association of a beverage tax and no evidence of substitution to high-sugar foods among independent store shoppers.…”
Section: Jama Network Open | Health Policymentioning
confidence: 63%
“…Mounting research suggests that beverage taxes are consistently associated with increased prices, 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 and reductions in the volume of taxed beverages sold 13 , 14 , 15 , 19 , 20 , 21 , 22 , 23 , 24 with considerable variation by retailer type and tax jurisdiction. There is some evidence that beverage taxes are associated with reductions in self-reported consumptions of SSBs, although results are mixed and many studies are limited by small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…We found that upon tax implementation, sweetened beverage consumption decreased substantially among lower-income families in Seattle, as well as low-income families living in nearby cities that share the same media market as Seattle [ 9 ]. Additionally, Cawley et al [ 10 ] noted that studies of beverage taxes that use a nearby comparison area find smaller differential changes in beverage consumption between taxed and nearby untaxed areas compared to studies that use a more distant comparison area; this could be due to multiple causes, including sharing a media market, confusion about which areas are taxed, and being exposed to messaging about the tax.…”
Section: Introductionmentioning
confidence: 99%